Adsorption of copper ions from aqueous solutions by modified alginate beads / Muhamad Zharif Md. Isa and Faraziehan Senusi - Md. Isa, Muhamad Zharif; Senusi, Faraziehan (2020)
The performance of modified polyphenolic alginate bead on their ability to adsorb copper ions in water was studied. The aim of the study is to determine the effect of tannic acid content on the modification of immobilized alginate beads for copper ions removal, evaluate the effect of pH, initial concentration and adsorbent dosage on the heavy metal removal and study on the adsorption kinetic and isotherm model. The experimental works started with the preparation of immobilized alginate beads and modification of immobilized alginate beads by tannic acid. Then, batch adsorption process and the characterization of the samples were conducted. Based on the result, the removal amount of Cu2+ ions increase from the pH solution of 2 to 7 where the amount of metal uptake increases from 0.003 mg/g to 1.457 mg/g and reach optimum. From 0.50 g of the adsorbent dosage used, the amount of metal ions adsorbed achieved about 0.69 mg/g and it increases gradually 1.007 mg/g at 2.0 g dosage and the dosage tended to be constant. The adsorption quantity of Cu2+ is 0.029 mg/g for initial concentration for 1 ppm of the solution and it increases to 0.906 mg/g when the initial concentration of the solution is 10 ppm. The kinetic and isotherm model for this study were Pseudo first-order kinetic model and Langmuir isotherm model respectively based on the better linear plot and correlation coefficient R2 value.